2014
DOI: 10.4236/ajps.2014.51008
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Phylogeny Determined Using Chloroplast DNA Inferred a New Phylogenetic Relationship of <i>Rorippa aquatica</i> (Eaton) EJ Palmer & Steyermark (Brassicaceae)—Lake Cress

Abstract: North American lake cress, Rorippa aquatica (Eaton) EJ Palmer & Steyermark (Brassicaceae), is listed as an endangered or threatened species. Lake cress shows heterophyllic changes in leaf form in response to the surrounding environment. Therefore, this species has received considerable attention from ecological and morphological perspectives. However, its phylogenetic position and taxonomic status have long been a subject of debate. To analyze the phylogenetic relationship of lake cress, we investigated chloro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 15 publications
1
11
0
Order By: Relevance
“…With the rise of sequencing technology, transcriptome analysis has indicated that light intensity affects leaf form alterations in North American lake cress, Rorippa aquatica (Brassicaceae) [44,45]. In North American lake cress, dissected leaves with deep biserrated leaflets developed under higher light intensity (90 μmol photons m −2 s −1 ) whereas dissected leaves with a relatively smooth margin developed when exposed to lower light intensity (15 μmol photons m −2 s −1 ).…”
Section: Environmental Factors That Induce Heterophyllymentioning
confidence: 99%
See 1 more Smart Citation
“…With the rise of sequencing technology, transcriptome analysis has indicated that light intensity affects leaf form alterations in North American lake cress, Rorippa aquatica (Brassicaceae) [44,45]. In North American lake cress, dissected leaves with deep biserrated leaflets developed under higher light intensity (90 μmol photons m −2 s −1 ) whereas dissected leaves with a relatively smooth margin developed when exposed to lower light intensity (15 μmol photons m −2 s −1 ).…”
Section: Environmental Factors That Induce Heterophyllymentioning
confidence: 99%
“…The plant develops pinnately dissected leaves with needle-like leaf blades under submerged conditions, while it forms simplified leaves with serrated margins under terrestrial conditions. Interestingly leaf shape alternation is induced by changes in ambient temperature [44,45]. Lower temperatures result in more dissected leaves, which resemble submerged leaves, and higher temperatures simplify the leaf shape.…”
Section: Molecular Basis For Heterophyllymentioning
confidence: 99%
“…Therefore, the extensive knowledge on leaf development accumulated from these compound-and simple-leafed model species may help to reveal the molecular mechanism regulating heterophylly in R. aquatica. Indeed, studies on submergence tolerance in Rorippa species have been successfully performed based on comparisons with Arabidopsis (Akman et al, 2012;Sasidharan et al, 2013), and phylogenetic and modeling-based analyses have also been reported (Nakamasu et al, 2014;Nakayama et al, 2014). These features make R. aquatica an excellent model species to investigate the mechanism regulating heterophylly.…”
Section: Introductionmentioning
confidence: 99%
“…Rorippa aquatica (Brassicaceae) propagates asexually by plantlet regeneration from leaf explants in nature [ 2 , 3 ]. R. aquatica is an amphibious plant belonging to the Brassicaceae family and it inhabits rivers and lakesides in North America [ 4 , 5 ]. It is often difficult to study plant species which regenerate plantlets in nature because of their properties (e.g., long term plantlet regeneration and poor genetic information).…”
Section: Introductionmentioning
confidence: 99%
“…It is often difficult to study plant species which regenerate plantlets in nature because of their properties (e.g., long term plantlet regeneration and poor genetic information). R. aquatica requires only two weeks for plantlet regeneration [ 2 ] and it belongs to the same family as A. thaliana [ 5 ]. Some previous studies have revealed the molecular mechanisms underlying leaf development and plantlet regeneration [ 2 , 4 ].…”
Section: Introductionmentioning
confidence: 99%